Retrospective /Backlog Cataloguing: The Experience at the University of Cape Coast Library, Cape Coast - Ibrahim, A-K; Kofi, C. (Ghana Library Journal, 2007)
This paper looked at retrospective cataloguing in the Library of the University of Cape Coast (UCC) from 1991 to 2004. It was discovered that over twelve thousand (12,000) volumes of books had not been processed or catalogued in this Library. This means that these materials did not have any traces in the public catalogue and therefore their retrieval was very difficult. To clear the backlog a cataloguer from a sister university library was engaged on contract from January to August 1994. By the end of the cataloguer’s contract a total of five thousand (5,000) volumes had been catalogued and their records provided in the public catalogues. This paper concludes by suggesting to the library management that librarians in the library be encouraged to take interest in cataloguing; that the Head of the Cataloguing Department be tasked with the responsibility of seeing to clear the backlog. Finally the paper also suggests that the services of students could be used during holidays to work specifically on the backlog.